Factors Influencing The Sustainable Expansion Of Small Business Entities And Opportunities For Their Effective Use - Juraxanov Muzaffar Eskandarovich (The American Journal of Management and Economics Innovations, 2020)
The article deals with the analysis of the factors influencing the sustainable development of small business. At the same time, the indicators of sustainability of small businesses in Andijan region are analyzed and the opportunities for their effective use are highlighted.